Highly efficient and compatible shampoo for use after hair transplant - Schweiger D; Schoelermann AM; Filbry A; Hamann T; Moser C; Rippke F (Dove Medical Press, 2015)
Dorothea Schweiger,1 Andrea M Schoelermann,1 Alexander Filbry,1 Tina Hamann,1 Claudia Moser,2 Frank Rippke1 1Research and Development, Beiersdorf AG, Hamburg, Germany; 2Moser Medical, Clinics for Aesthetic Plastic Surgery, Vienna, Austria Background: Sensitive or hyperreactive skin is a common condition defined by prickling, burning, pain, and pruritus. Although this skin problem was initially described on the face, the scalp is often affected. A sensitive scalp can react with irritation to harsh surfactants or other additives which are often present in shampoos. For this reason, we developed a new rinse-off hypertolerant shampoo specifically designed for the hypersensitive and problematic scalp.Methods: The shampoo formulation is based on an extremely mild surfactant system and contains bisabolol, an anti-irritant and anti-inflammatory ingredient of chamomile. The shampoo is free of additives such as perfumes, silicones, colorants, parabens, paraffins, and betaine. Since skin can remain in a hyperreactive state after wounding, the status after hair transplantation was chosen as a model system to test the shampoo. Scalp condition and compatibility of each volunteer were analyzed by a plastic surgeon directly after hair transplant and after stitch removal. The plastic surgeons also rated whether they would recommend the further use of the test shampoo. Additionally, volunteers completed a self-assessment questionnaire.Results: Following hair transplantation, regular use of the shampoo resulted in a significant reduction in the extent of scabbing and erythema. This was confirmed by dermatological scalp examinations performed by the plastic surgeon as well as in volunteers' self-assessments. The plastic surgeon highly recommended the further use of the test shampoo after hair transplant to all study participants.Conclusion: Application of the test shampoo demonstrated excellent skin compatibility and product efficacy after hair transplant. The test shampoo significantly reduced the extent of scabs and erythema. Therefore, the shampoo is ideally suited for use after hair transplantation and for the treatment of sensitive scalp. The excellent skin compatibility is because of the mild surfactant system, the calming ingredient bisabolol, and the absence of potentially irritating ingredients.Keywords: sensitive, scalp, shampoo, bisabolol, hair transplant